Overview of directions of improving the simulation of severe accidents based on the experience of the Tree Mile Island NPP - Козлов, Игорь Леонидович (Eastern-European Journal of Enterprise Technologies, 2015)
After the accident at the 2nd unit of the Three Mile Island NPP (USA) in 1979, scientists and experts of the world nuclear community came to the unequivocal conclusion on the need for deeper study of the causes and consequences of severe accidents. Simulation and analysis of severe accidents are the fundamental basis of guidelines/instructions, regulating the strategies and actions of the emergency management staff. Therefore, the simulation adequacy and validity of emergency processes determine the effectiveness of management strategies of severe accidents. An overview of known results of numerical simulation of the severe accident at the TMI-2 NPP, as well as the simulation results of containment destruction processes in severe accidents in tank reactors was presented. Based on the analysis, the basic directions of improving the methodological support in the simulation of steam-gas explosions taking into account the reasonableness of the choice of modes and conditions of using the calculation methods (codes) with their subsequent verification and validation based on the example of the Fukushima severe accidents were determined.